The Effect of Using Videoscribe as a Teaching Media on Writing Descriptive Text of the Tenth Grade Students of SMK YPSEI Palangka Raya - I Nyoman Trio Satya Sudana; Ristati; Tampung N Saman (The Study Program of English Education of Palangka Raya University, 2021)
Learning Process during pandemic covid-19 has become harder for teacher and students. The learning process has to encourage, motivate, and stimulate the students so the learning process can be done effectively. This study aims to find out the effect of using videoscribe as a teaching media on writing descriptive text of the tenth grade students of SMK YPSEI Palangka Raya. The research subject was the tenth grade students of SMK YPSEI Palangka Raya. This Study is a quantitative method that using Randomized-Groups Pre-Test-Post-Test Control Group Design. The instrument that used was writing descriptive. The data were collected in several steps: pre-test, treatment, and post-test; the data were processed in several steps: collecting data, scoring, and calculating; data analysing was conducted using SPSS application including tests of data normality and tests of Hypothesis. The data analysing was conducted using Non-parametric tests on two paired samples which was Wilcoxon Sign Rank test. The result of this study conclude that the use of videoscribe as a teaching media has significant effect for the students in writing descriptive text.